2015
DOI: 10.1186/s12904-015-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

The application of the palliative prognostic index, charlson comorbidity index, and Glasgow prognostic score in predicting the life expectancy of patients with hematologic malignancies under palliative care

Abstract: BackgroundThe clinical course for hematologic malignancy varies widely and no prognostic tool is available for patients with a hematologic malignancy under palliative care. To assess the application of the Palliative Prognostic Index (PPI), Charlson Comorbidity Index (CCI), and Glasgow Prognostic Score (GPS) as prognostic tools in patients with hematologic malignancies under palliative care.MethodsWe included 217 patients with pathologically proven hematologic malignancies under palliative care consultation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
1
25
0
2
Order By: Relevance
“…The accuracy of prognostication was even improved by concurrent use of the Glasgow Prognostic Score and the Charlson Comorbidity Index [39], but their impact as prognosticator to identify patients in need of SPC remains to be verified.…”
Section: Potential Indications For Palliative Care Needmentioning
confidence: 99%
“…The accuracy of prognostication was even improved by concurrent use of the Glasgow Prognostic Score and the Charlson Comorbidity Index [39], but their impact as prognosticator to identify patients in need of SPC remains to be verified.…”
Section: Potential Indications For Palliative Care Needmentioning
confidence: 99%
“…This could be attributed to the Chou et al. () and Ohno et al. () studies having shorter time frames of survival in their populations (16 days and 6.4 weeks respectively) than was the aim of this study, to identify risk of deteriorating and dying within 3–6 months.…”
Section: Discussionmentioning
confidence: 85%
“…A recent systematic review of prognostic factors present in the final 3 months of life revealed that the body of knowledge is predominantly focused on people who are admitted to the intensive care unit, or are treated aggressively (Button et al, 2017b). Few studies have explored prognostic factors or prognostic tools to inform transitioning to end-of-life care for people with a haematological malignancy (Button et al, 2017a;Chou et al, 2015;Corbett, Johnstone, McCracken Trauer, & Spruyt, 2013;Kripp et al, 2014;Ohno, Abe, Sasaki, & Okuhiro, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Validation studies of the PPI were performed in Japan, Taiwan, Kuwait, Ireland, the United Kingdom, and Australia [39][40][41][42][43][44][45][46]. Morita et al revealed that the PPI signiicantly reduced overestimation of survival compared to the CPS [39].…”
Section: Risk Groupsmentioning
confidence: 99%
“…There are some comparative studies [9,43,67], and the largest is the J-ProVal study reported by Baba et al…”
Section: Direct Comparison Of Diferent Prognostic Models In the Same mentioning
confidence: 99%